Study of disulfide-based di-epoxy resin as an anti-corrosive paint with modification by graphene and carbon nanotube - Patel, Jay K.; Joshi, Medha; Desai, Dhaval; Wale, Apparav K. (Journal of the Indian Chemical Society, 2026)
In this study, we synthesized a disulfide-based epoxy resin using dithiodibenzoic acid in combination with epichlorohydrin and a caustic additive. The identification of the epoxide group was confirmed by IR, NMR, and Epoxy equivalent weight. The thermal stability was investigated using a thermogravimetry curve. Surface morphology of paint samples was investigated by SEM. Paint was prepared with the addition of zinc powder, zinc phosphate, calcium carbonate, along with fillers, additives, and solvents like butanone and xylene, an aromatic polyamine adduct hardener. The paint was modified by the addition of 1.0 wt% graphene and 0.05 wt% carbon nanotube (CNTs), and compared its anticorrosion application against an unmodified paint sample. The result suggested that the addition of graphene and CNTs enhanced the mechanical strength of the paint and also improved the chemical resistance against corrosion.
Keywords: Anticorrosive properties; CNTs; Coating; Epoxy resin; graphene; Mechanical characteristics